2019
DOI: 10.18410/jebmh/2019/143
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Clinical Evaluation of Oral Clonidine vs. Pregabalin Premedication for Attenuation of Haemodynamic Response to Laryngoscopy and Intubation- A Prospective Randomised Double Blinded Placebocontrolled Study

Abstract: BACKGROUNDEndotracheal intubation is considered gold standard in patients undergoing general anaesthesia. Direct laryngoscopy and tracheal intubation result in an increase in blood pressure and heart rate, the so called 'pressor response'. Various techniques and drugs have been used in the past to attenuate the pressor response, however none has been proved to be ideal. We conducted this study to compare any possible blunting of cardiovascular effects of laryngoscopy and tracheal intubation by the use of 150 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…They observed that clonidine (200 µg) is better in decreasing the HR as compared to pregabalin (150mg) which was statistically significant after induction and 10 min post laryngoscopy and intubation. 18 Both clonidine (200 µg) and pregabalin (150mg) provided adequate anxiolysis and sedation in preoperative period which is in accordance with studies conducted by Gupta et al, Chandra et al and Waikar et al 13,15,19…”
Section: Discussionsupporting
confidence: 84%
“…They observed that clonidine (200 µg) is better in decreasing the HR as compared to pregabalin (150mg) which was statistically significant after induction and 10 min post laryngoscopy and intubation. 18 Both clonidine (200 µg) and pregabalin (150mg) provided adequate anxiolysis and sedation in preoperative period which is in accordance with studies conducted by Gupta et al, Chandra et al and Waikar et al 13,15,19…”
Section: Discussionsupporting
confidence: 84%
“…In other studies, Gupta et al, 14 Raichurkar et al, 15 Soni et al, 16 and Murari et al, 17 concluded that oral clonidine in a dose of 0.2 mg was effective in blunting sympathoadrenal responses HR to laryngoscopy and intubation.…”
Section: Discussionmentioning
confidence: 94%